A Critical Review on the Thermal Transport Characteristics of Graphene-Based Nanofluids - Thirumaran Balaji; Dhasan Mohan Lal; Chandrasekaran Selvam (Energies, 2023)
Over the past few years, considerable research work has been performed on the graphene-based nano-dispersion for improvement of the thermal conductivity and thermal characteristics of base fluid. Graphene-based dispersion shows the good stability, better enhancement in thermal conductivity, and heat transport behavior compared to the other nano-dispersions drawing significant attention among researchers. This article carries out comprehensive reviews on the heat transport behavior of graphene-based nano-dispersion over the past ten years. Some researchers have carried out the investigations on the various methods adopted for the preparation of graphene-based nano-dispersion, techniques involved in making good dispersion including stability characterizations. There needs to be a better agreement in results reported by the various researchers, which paves the way for further potential research needs. Some researchers studied thermo-physical properties and heat transport behavior of graphene nanofluids. Only a few researchers have studied the usage of graphene nanofluids in various fields of application, including automobile radiators, electronics cooling, heat exchangers, etc. This article reviews the different challenges faced during its development in broad areas of application, and this could be a referral to have explicit knowledge of graphene dispersions with their characterization. Moreover, this study explores the various parameters that influence the effective thermal conductivity and heat transport behavior of the graphene dispersions for the various heat transport applications, which could be a reference guide to find the potential benefits as well as drawbacks of the graphene-based nano-dispersion for future research works.